The genera Hoplammophila de Beaumont, 1960 and Sceliphron Klug, 1801 (Hymenoptera: Sphecidae) in Vietnam - Phong, Pham Huy; Duong, Tran Dinh; Tu Anh, Nguyen Thi (Academia Journal of Biology, 2025)
The genera Hoplammophila de Beaumont, 1960 and Sceliphron Klug, 1801 (Hymenoptera: Sphecidae) in Vietnam are studied. The genus Hoplammophila, with a single species and the genus Sceliphron, with two species and five subspecies are recorded. Two species Hoplammophila aemulans (Kohl, 1901) and Sceliphron coromandelicum (Lepeletier de Saint-Fargeau, 1845), are reported for the first time from Vietnam. Notes on the nest structure of S. coromandelicum, a key to the species and subspecies of the Vietnamese Sceliphron and their new distributional records are presented.